Ceramics of the Merv Oasis – The other side. (September 2022) - Puschnigg, Gabriele
Abstract: Ceramic studies at Merv have a long tradition and include distinct academic schools and diverse analytical approaches. In this contribution, I critically evaluate research strategies and the analysis of data generated from the international field work and excavations of the 1990s and early 2000s. My original study of the ceramics from these excavations focused on quantitative and statistical methods of analysis to gain insights into the chronological and stylistic developments of this large and rich assemblage. In the present paper, I take a different stance, highlighting individual observations that were left out of the initial examination to provide a complementary perspective on the pottery but also to illustrate the constraints emerging from the way the material was recorded and documented. These observations are related to aspects of vessel shaping, surface treatments, decorative features and incised marks, which are further situated within the wider context of Central Asian ceramics.